First records of bats (Mammalia: Chiroptera) from Son La city, Northwestern Vietnam, with remarks on their conservation status - Loi, Dao Nhan (Academia Journal of Biology, 2019)
Son La is a well-known city in the Northwestern region of Vietnam for its outstanding landscapes. It contains a variety of ecosystems ranging from farming area, valleys, forests on hills and karst with cave systems. Natural habitats of the city would be suitable for many bat species. However, bats of the city were not included in any literature. Between March 2014 and June 2018, we conducted a series of bat surveys in this city using mist nets and harp traps. Results from our study indicated that Son La city is a home to at least 21 bat species belonging to 9 genera, 6 families. Of which, Rhinolophus thomasi was listed as “VU” (Vulnerable) in the 2007 Red Book of Vietnam and Myotis annamiticus was listed in the IUCN Redlist of the Threatened Species as “DD” (Data Deficient). This paper provides the first data on bats of Son La city with morphological measurements and conservation status of each recorded species.